2017
DOI: 10.18203/2349-3933.ijam20170123
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum magnesium levels in diabetes mellitus and its correlation with complications (retinopathy and HbA1c) a cross-sectional study of one year

Abstract: Background: Diabetes mellitus is a heterogeneous group of metabolic disorders characterized by chronic hyperglycemia with disturbance of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action or both. The aim of this study was to estimate serum magnesium levels in patients with type 2 diabetes mellitus and correlate it with complications of type 2 diabetes mellitus - glycemic control and retinopathy.Methods: A cross-sectional study of 100 patients with type 2 diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Also, Kareem et al, observed a low serum magnesium level in diabetic patients and the level was lowest in patients with diabetic retinopathy [9]. This is also similar to the findings of Saproo & Singh, who revealed low magnesium levels in diabetic patients and concluded that it can be used as a marker to predict retinopathy [5] . Peters et al, suggested that extracellular and intracellular magnesium deficiency is typical in chronic, stable, mild type 2 diabetes and may be an independent risk factor for the development of the excess cardiovascular complications associated with diabetes [10].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Also, Kareem et al, observed a low serum magnesium level in diabetic patients and the level was lowest in patients with diabetic retinopathy [9]. This is also similar to the findings of Saproo & Singh, who revealed low magnesium levels in diabetic patients and concluded that it can be used as a marker to predict retinopathy [5] . Peters et al, suggested that extracellular and intracellular magnesium deficiency is typical in chronic, stable, mild type 2 diabetes and may be an independent risk factor for the development of the excess cardiovascular complications associated with diabetes [10].…”
Section: Discussionsupporting
confidence: 68%
“…Also, there was significant negative correlation between serum magnesium and serum potassium, creatinine, grade of nephropathy and A/C ratio ( p=0.003, 0.001, 0.001, 0.001, respectively). While, a positive correlation was found between serum magnesium and serum sodium and glomerular filtration rate (p=0.003, 0.001, respectively) as shown in Table ( 5) and Figs. (1-4).…”
Section: Laboratory Data Among Studied Groupsmentioning
confidence: 75%
See 1 more Smart Citation
“…The contributions of micronutrients as potential preventive and therapeutic agents are being investigated in patients of Diabetes Mellitus and their micro vascular and macro vascular complications. 1 Diabetic patients have found to suffer from abnormalities in their zinc, chromium, copper, magnesium and manganese levels. 2 The role of magnesium nowadays is of great scholarly and clinical interest in Diabetes Mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…5 The possible reason for this deficiency may be the necessity of magnesium for insulin receptor interaction, its secretion, post receptor events like tyrosine kinase mediated phosphorylation and carbohydrate utilization. 1,6 If any of these functions are compromised, it leads to insulin resistance. This is contributed by a) Hyperglycemia, which leads to a further decrease in cellular Mg levels, independent of insulin levels, b) increase urinary Mg loss due to osmotic diuresis c) use of hypolipidemic agents and diuretics increasing urinary Mg loss.…”
Section: Introductionmentioning
confidence: 99%